Rút gọn phân thức 8x^3+y^3/y^3+2xy^2+y^2-4x^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(A=\dfrac{\left(2x-y\right)^2\cdot\left(2x+y\right)\left(4x^2+2xy+y^2\right)}{2x\left(2x+y\right)\left(2x-y\right)^2}=\dfrac{4x^2+2xy+y^2}{2x}\)
1. \(\dfrac{x^3-4x^2+4x}{x^2-4}=\dfrac{x\left(x^2-4x+4\right)}{\left(x+2\right)\left(x-2\right)}=\dfrac{x\left(x-2\right)^2}{\left(x+2\right)\left(x-2\right)}=\dfrac{x\left(x-2\right)}{x+2}\)
a) (x+3)(x^2-3x+9)-(54+x^3)
= x^3- 3x^2+9x+3x^2-9x+27-54-x63
= -27
b) (2x + y)(4x^2 – 2xy + y^2) – (2x – y)(4x^2+ 2xy + y^2)
= (2x + y)[(2x)^2 – 2x.y + y^2] – (2x – y)[(2x)^2 + 2x.y + y^2]
= [(2x)3^3+ y^3] – [(2x)^3 – y^3]
= (2x)^3 + y^3 – (2x)^3 + y^3
= 2y^3
a)(x+3)(X^2-3x+9)-(54+x^3)
= \(x^3\)+ \(3^3 \) - 54 -\(x^3\)
= 27- 54
= -27
b)(2x+y)(4x^2-2xy+y^2)-(2x-y)(4x^2+2xy+y^2)
= \((2x)^3\) + \(y^3\) - [\((2x)^3\) - \(y^3\) ]
= \(8x^3\) + \(y^3\) - \(8x^3\) + \(y^3\)
= \(2y^3\)
\(a.\)
\(\dfrac{16x^2-1}{16x^2-8x+1}\\ =\dfrac{\left(4x\right)^2-1}{\left(4x-1\right)^2}\\ =\dfrac{\left(4x-1\right)\left(4x+1\right)}{\left(4x-1\right)^2}\\ =\dfrac{4x+1}{4x-1}\)
\(b.\)
\(\dfrac{4x^2-4xy+y^2}{-\left(4x^2-y^2\right)}\\ =-\dfrac{\left(2x-y\right)^2}{\left(2x-y\right)\left(2x+y\right)}\\ =\dfrac{-\left(2x-y\right)}{2x+y}\\ =\dfrac{y-2x}{y+2x}\)
a) Ta có: \(\dfrac{16x^2-1}{16x^2-8x+1}\)
\(=\dfrac{\left(4x-1\right)\left(4x+1\right)}{\left(4x-1\right)^2}\)
\(=\dfrac{4x+1}{4x-1}\)
b) Ta có: \(\dfrac{4x^2-4xy+y^2}{y^2-4x^2}\)
\(=\dfrac{\left(2x-y\right)^2}{\left(y-2x\right)\left(y+2x\right)}\)
\(=\dfrac{\left(y-2x\right)^2}{\left(y-2x\right)\left(y+2x\right)}\)
\(=\dfrac{y-2x}{y+2x}\)
b) \(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)
\(=\left(2x+y\right)\left(4x^2-2xy+y^2\right)+\left(2x+y\right)\left(4x^2+2xy+y^2\right)\)
\(=\left(2x+y\right)\left(4x^2-2xy+y^2+4x^2+2xy+y^2\right)\)
\(=\left(2x+y\right)\left(8x^2+2y^2\right)\)
\(=\left(2x+y\right)\left(4x+y\right).2xy\)
Bài 1:
\(\dfrac{8x^3+y^3}{y^3+2xy^2+y^2-4x^2}\\ =\dfrac{\left(2x+y\right)\left(4x^2-2xy+y^2\right)}{\left(y^3+2xy^2\right)+\left(y^2-4x^2\right)}\\ =\dfrac{\left(2x+y\right)\left(4x^2-2xy+y^2\right)}{y^2\left(y+2x\right)+\left(y-2x\right)\left(y+2x\right)}\\ =\dfrac{\left(y+2x\right)\left(4x^2-2xy+y^2\right)}{\left(y+2x\right)\left(y^2+y-2x\right)}\\ =\dfrac{4x^2-2xy+y^2}{y^2+y-2x}\)
\(\dfrac{8x^3+y^3}{y^3+2xy^2+y^2-4x^2}\)
\(=\dfrac{\left(2x+y\right)\left(4x^2-2xy+y^2\right)}{y^2\left(y+2x\right)+\left(y+2x\right)\left(y-2x\right)}\)
\(=\dfrac{4x^2-2xy+y^2}{y^2+y-2x}\)